INTEREST AND IMPLEMENTATION: PROBING THE AUDIO-VISUAL MEDIA INTEGRATION OF SENIOR HIGH SCHOOL ENGLISH TEACHERS - Rahmawati, Fitria (Epigram, 2024)
Audio-visual media are among the most common media teachers use in English instructional process. Audio-visual media are tools used to deliver information with both audio and visual components. As it possesses both characteristics, this type of media has much potential. The purposes of this study were to (1) identify the level of senior high school (SHS) English teachers’ interest in using audio-visual media to teach the English language and (2) explore the implementation of audio-visual media by SHS English teachers. This study was conducted using a quantitative approach adopting the survey design. The data were collected using a questionnaire. The respondents of this study were English senior high school teachers in one region of Central Java, Indonesia. A total of 65 teachers participated in this study, consisting of 24 (36.9%) male teachers and 41 (63.1%) female teachers. The results of this study showed that the teachers taught using audio-visual media. The result found that the SHS teachers had a “high interest” towards the use of audio-visual media to teach the English language, with a mean score of 3.38 of the total indicators of 4.00 and a standard deviation of .31. In addition, the use of audio-visual media in teaching the English language by SHS teachers is responded “meet expectation” with a mean score of 3.06 of the total indicators 4.00 and standard deviation .28. Through the calculation of EFA (Exploratory Factor Analysis), this study discovered three components regarding the implementation of audio-visual media, namely delivery, teacher role, and development. Thus, this study discovered that SHS English teachers have been able to use audio-visual media appropriately and acceptably.